Toward an Epistemic-Logical Theory of Categorization - Conradie, Willem; Frittella, Sabine; Palmigiano, Alessandra; Piazzai, Michele; Tzimoulis, Apostolos; Wijnberg, Nachoem M. (Electronic proceedings in theoretical computer science, 2017)
Categorization systems are widely studied in psychology, sociology, and organization theory as information-structuring devices which are critical to decision-making processes. In the present paper, we introduce a sound and complete epistemic logic of categories and agents' categorical perception. The Kripke-style semantics of this logic is given in terms of data structures based on two domains: one domain representing objects (e.g. market products) and one domain representing the features of the objects which are relevant to the agents' decision-making. We use this framework to discuss and propose logic-based formalizations of some core concepts from psychological, sociological, and organizational research in categorization theory.